BMC Medicine - Lee, Lin.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Medicine is the flagship medical journal of the BMC series. An open access, transparent peer-reviewed general medical journal, BMC Medicine publishes outstanding and influential research in all areas of clinical practice, translational medicine, medical and health advances, public health, global health, policy, and general topics of interest to the biomedical and sociomedical professional communities. .
Keywords: Medical sciences; Public health; Epidemiology; Cancer; Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Medicine; Health Sciences; Public Health; Epidemiology; Cancers; Biomedical Research; Clinical Medicine